Dose Monitoring in Radiology Departments: Status Quo and Future Perspectives - Boos, J.; Meineke, A.; Bethge, O. T.; Antoch, G.; Kröpil, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
The number of computed tomography examinations has continuously increased over the last decades and accounts for a major part of the collective radiation dose from medical investigations. For purposes of quality assurance in modern radiology a systematic monitoring and analysis of dose related data from radiological examinations is mandatory. Various ways of collecting dose data are available today, for example the Digital Imaging and Communication in Medicine – Structured Report (DICOM-SR), optical character recognition and DICOM-modality performed procedure steps (MPPS). The DICOM-SR is part of the DICOM-standard and provides the DICOM-Radiation Dose Structured Report, which is an easily applicable and comprehensive solution to collect radiation dose parameters. This standard simplifies the process of data collection and enables comprehensive dose monitoring. Various commercial dose monitoring software devices with varying characteristics are available today. In this article, we discuss legal obligations, various ways to monitor dose data, current dose monitoring software solutions and future perspectives in regard to the EU Council Directive 2013/59/EURATOM.Key Points:• Automated, systematic dose monitoring is an important element in quality assurance of radiology departments. • DICOM-RDSR-capable CT scanners facilitate the monitoring of dose data. • A variety of commercial and non-commercial dose monitoring software tools are available today. • Successful dose monitoring requires comprehensive infrastructure for monitoring, analysing and optimizing radiation exposure. Citation Format:• Boos J, Meineke A, Bethge OT et al. Dose Monitoring in Radiology Departments: Status Quo and Future Perspectives. Fortschr Röntgenstr 2016; 188: 443 – 450
Keywords: dose monitoring; computed tomography; radiation dose; DICOM; structured report